Uplift Bearing Capacity of Transmission Tower Foundation in Reinforced Aeolian Sand Using Simplified Model Tests - Shijun Ding; Yongfeng Cheng; Hong Zheng; Feng Xue; Zhibao Nie; Yin Man (Advances in Civil Engineering)
In order to analyze the uplift bearing capacity of transmission tower foundation in the geosythetic-reinforced aeolian sand, a series of simplified indoor modeling tests are carried out. A simplified reduced-scale foundation made according to the prototype and the uplift bearing capacity of transmission tower foundation in geosynthetic-reinforced aeolian sand is studied. Three kinds of reinforcement materials are embedded in the sand according to five ways of layout spacing. A total of 15 reinforcement schemes are tested. The results show that ultimate uplift bearing capacity of transmission tower foundation can be significantly improved by the reinforcement treatment of geotechnical materials in the aeolian sand. The type and spacing of reinforced materials also have a significant influence on the uplift bearing capacity of the foundation model in reinforced aeolian sand, and the effect of reinforcement works until the end of the loading process. The comprehensive effect is evaluated by the ratio of bearing capacity improvement and the total layer of reinforced materials. Based on the above results, the bearing mechanism of transmission tower foundation in geosynthetic-reinforced aeolian sand is elaborated and analyzed in detail.